50 years of informatics research on decision support: What's next - Mitchell, J. A. (Institutional Knowledge at Singapore Management University, 2011)
Objectives: To reflect on the history, status, and future trends of decision support in health and biomedical informatics. To highlight the new challenges posed by the complexity and diversity of genomic and clinical domains. To examine the emerging paradigms for sup - porting cost-effective, personalized decision making. Methods: A group of international experts in health and biomedical informatics presented their views and discussed the challenges and issues on decision support at the Methods of Information in Medicine 50th anniversary symposium. The experts were invited to write short articles summarizing their thoughts and positions after the symposium. Results and Conclusions: The challenges posed by the complexity and diversity of the domain knowledge, system infrastructure, and usage pattern are highlighted. New requirements and computational paradigms for representing, using, and acquiring biomedical knowledge and healthcare protocols are proposed. The underlying common themes identified for developing next-generation decision support include incorporating lessons from history, uniform vocabularies, integrative interfaces, contextualized decisions, personalized recommendations, and adaptive solutions. © Schattauer 2011.